An 'Angela Merkel Effect'? The Impact of Gender on CDU/CSU Voting Intention between 1998 and 2013. Issue 1 (2nd January 2017) - Debus, Marc
Abstract : By referring to the theoretical and empirical literature on 'same gender voting' and the 'modern gender gap', this contribution aims to analyse whether gender played a role in party choice in Bundestag elections. We concentrate on the time period between 1998 and 2013, enabling us to cover three elections while Angela Merkel was the chancellor candidate of CDU and CSU (2005, 2009 and 2013), while she was CDU party chair (2002) and while no women served as chancellor candidate or party chair of CDU and CSU. The results of a dataset compiled from five German national election studies show that women were not more likely to opt for the CDU/CSU since the nomination of Angela Merkel as chancellor candidate, nor were they less likely to vote for the Christian Democrats due to their rather conservative programmatic profile on the order of society.